Pengaruh Kepemimpinan dan Motivasi Kepala Sekolah Terhadap Disiplin Kerja Guru - Bernia, Reisa (Journal of Innovation in Teaching and Instructional Media, 2024)
This systematic literature review examines the influence of principal leadership and motivation on teacher discipline. This study aims to synthesize empirical findings from recent research in Southeast Asia to understand the complex relationships between leadership approaches, strategic motivation, and teacher discipline outcomes. Using the PRISMA protocol, 15 peer-reviewed articles published between 2019-2024 were systematically analyzed from multiple electronic databases. The results show that principal leadership influences teacher discipline through multiple pathways, with transformational and democratic leadership styles showing the strongest positive effects. The study found that psychological empowerment, emotional intelligence, and organizational justice act as crucial mediating factors. The relationship between principal leadership and teacher discipline is strengthened when leaders create an environment that supports innovation, collaboration, and professional growth. The novelty of this study lies in the comprehensive analysis of mediating and moderating factors that influence the effectiveness of principal leadership in building teacher discipline. This study contributes to educational leadership theory and practice by providing evidence-based insights for school leaders to develop more effective strategies in improving teacher discipline through an integrated leadership and motivation approach.